CALCULATION OF CORRECTION FACTORS FOR EPITHERMAL NEUTRON SELF-SHIELDING IN Au-197 - Phạm Ngọc Sơn; Bạch Như Nguyện; Trịnh Thị Tú Anh; Nguyễn Đắc Châu (Tạp chí Khoa học Đại học Đà Lạt)
The epithermal neutron self-shielding correction factors for 197Au(n,g)198 reaction in Au target foils with different thickness were calculated using the Monte Carlo simulation code MCNP5. In this research, the characteristics of neutron irradiation facility at the thermal column of the Dalat Nuclear Research Reactor were used as the input parameters for the neutron source definition. The input epithermal neutron energy spectrum is defined as 1/E distribution from 0.5 eV to 0.2MeV.